SOSIALISASI PENDAMPINGAN PEMBELAJARAN BERBASIS GAMIFIKASI DI SDN TANJUNGSARI 1 KABUPATEN TULUNGAGUNG - Nugrananda Janattaka; Nourma Okaviarini (Kanigara, 2022)
Technology-based learning is a form of adaptation of education to technological advances. The development of technological advances has led the world of education to adapt to global demands, both in the learning process and in the use of learning media. Gamification in the world of education can be defined to include game elements and elements in the learning environment, both the learning process and learning evaluation. The purpose of mentoring socialization at SDN Tanjungsari 1 is to introduce gamification support applications in education so that they can create innovative and interactive learning. The supporting applications used in this mentoring socialization are quizwhizzer and genially. The supporting application is an application that is quite easy to use and also has an attractive interface for elementary students. Mentoring is carried out twice, namely first discussing the use of quizwhizzer and making game elements in the quiz that will be applied. Meanwhile, at the second meeting, it was the use of genially in supporting learning using gamification in the form of online board games that were integrated with the ongoing learning theme.